PERBEDAAN PERSEPSI AKADEMISI DAN PRAKTISI AKUNTANSI TENTANG AKUNTANSI FORENSIK SEBAGAI MATA KULIAH - Mukhlas Adi Putra (JURNAL STIE SEMARANG, 2018)
This study aims to analyze the difference between academics and practitioners perceptions about interest, relevance, methods of integration, continuing education, and competency of forensic accountants. Object of research was academics with practitioners in the province of Central Java. This research was empirical study using purposive sampling technique in data collection. Data was obtained by distributing questionnaires by 196 universities in Central Java and government institutions BPKP and BPK representation of Central Java. A total of 165 respondents (84.18%) consisting of 78 people from academia, and 87 people from the practitioner has provided a responses. Data was analyzed by Independent Sample t Test with IBM SPSS version 21 software package. Hypothesis testing results indicate that there are significant differences in perception between academics and practitioners on forensic accounting as course.